Human-robot teaming and coordination in dynamic environments - Liu, Xiangyu (Nanyang Technological University, 2020)
As robots that sharing environments with humans proliferate, human-robot teamwork is becoming increasingly important. It is foreseeable that there will be more and more teams which are composed of humans and robots engaged in daily work. The integration of the appropriate decision-making process is an essential part of the design and development of an autonomous robot [1]. However, the simple decision trees cannot let robots to make complex decisions to satisfy the requirements of human-robot teaming. Letting human and robots work as a team is not just let human to control the robot directly, as there will be a degradation of trust which has bad influence on the work efficiency if the expectations of human do not match robots’ actions.